Developing Optimization Strategy for Dead Stock Inventory: Study Case for PT ABC - Trihapsari, Anggita Laras (CV. Publikasi Indonesia, 2024)
This study addresses the critical issue of inventory management at PT. ABC is a leading food and beverage company in Indonesia, focusing on reducing slow-moving and deadstock materials. The research employs a quantitative and qualitative approach, combining in-depth interviews with key personnel and analysis of secondary data from company records and industry guidelines. The study identifies the root causes of inventory inefficiencies. The findings lead to the development of targeted strategies to optimize inventory management and enhance operational efficiency. The study's recommendations include both short-term and long-term solutions, aiming to reduce deadstock levels and improve overall material management practices at PT ABC.